RETRACTED: Narasipuram et al. Analysis of Scalable Resonant DC–DC Converter Using GaN Switches for xEV Charging Stations. World Electr. Veh. J. 2024, 15, 218 - Rajanand Patnaik Narasipuram; Subbarao Mopidevi; Anton Dianov; Amit Singh Tandon (World Electric Vehicle Journal)
The journal retracts the article titled “Analysis of Scalable Resonant DC–DC Converter Using GaN Switches for xEV Charging Stations” [...]